Dedifferentiated endometrioid adenocarcinoma with trophoblastic components: Prolonged remission after treatment with bleomycin, etoposide, and cisplatin - Alexa K. Martin; Elizabeth G. Jackson; Henry D. Edwards; Michael P. Stany (Elsevier, 2020)
Dedifferentiated endometrial adenocarcinoma (DEAC) with trophoblastic components is a rare neoplasm with an aggressive behavior and a poor prognosis. Only seven cases have been reported in the literature. We present a 61-year-old patient who was diagnosed with Stage IB dedifferentiated endometrioid adenocarcinoma with trophoblastic elements. A post-operative β-hCG was elevated at 1877 mIU/mL. The patient received 6 cycles of carboplatin and paclitaxel with normalization of β-hCG; however, three months after completion of chemotherapy, her β-hCG increased to 39 mIU/mL and a mass overlaying the psoas muscle was noted on imaging. The mass was resected and confirmed to be recurrent disease. Four cycles of bleomycin, etoposide, and cisplatin were administered, and the patient remains without evidence of disease 3 years after completing treatment. Due to the small number of reported cases of DEAC with trophoblastic components, there is limited information regarding the appropriate first-line adjuvant chemotherapy regimen.